The effect of parity, birth weight babies, pregnancy interval and a history of hemorrhage with the incidence of postpartum hemorrhage (Case Study in the RSUD Ngudi Waluyo Wlingi Blitar on 2014) - Izfa Rifdiani (Universitas Airlangga, 2017)
Postpartum hemorrhage is one of the problems was the cause of maternal deaths in Indonesia. The maternal mortality rate is one indicator for the degree of health specially of a woman. Postpartum hemorrhage is bleeding or blood loss of 500 cc or more that occurred after the child is born. The research objective was to analyze the effect of parity, birth weight babies, pregnancy interval and a history of postpartum hemorrhage in the mother after giving birth to the incidence of postpartum hemorrhage in Ngudi Waluyo Hospital Wlingi Blitar 2014. This study used a case-control design. The populations in this study are all mothers who gave birth in Ngudi Waluyo Hospital Wlingi Blitar 2014. The sampling technique was simple random sampling. The results were obtained no effect of parity on the incidence of postpartum hemorrhage (OR=0,810, CI 95% 0,329<OR<1,995 , OR=0,895, CI 95% 0,260<OR<3,077), there was no effect of birth weight babies on the incidence of postpartum hemorrhage (OR=0,651, CI 95% 0,104<OR<4,096), there was effect of pregnancy interval on the incidence of postpartum hemorrhage (OR = 17.953, 95% CI 3.550 <OR <90.785) and there was effect of a history of bleeding on the incidence of postpartum hemorrhage postpartum (OR = 18.104, 95% CI 3.559 <OR <92.097). Health workers are expected to provide advice to the mother who gave birth to not be pregnant again during the next 2 years, and then advise the mother to join the family planning program in order to distance the pregnancy can be arranged. Examination of the precision of pregnant women visit each semester will make health care workers, pregnant women and families more aware of the possibility of postpartum hemorrhage after childbirth. Key words: parity, birth weight babies, pregnancy interval, a history of postpartum hemorrhage, the incidence of postpartum hemorrhage